Metabolomics profiling and antimicrobial activity of fermented date fruit Khastawi used as functional ingredients for making Asian confectionary dodol - Muhialdin, Belal J.; Marzlan, Anis Asyila; Kadum, Hana; Arulrajaha, Brisha; Mohamad Asri, Nursyafiqah; Fathallaha, Salahaldin; Meor Hussin, Anis Shobirin (Taylor & Francis, 2021)
Date fruit (Phoenix dactylifera) have long history in food application due to the nutritional value, pleasant flavour and biological activity. This study aimed at investigating the antimicrobial activity of date fruits fermented with Lactobacillus plantarum ATCC8014. The fermented date fruit was added as ingredient for confectionary making and evaluated for it is effects on the physiochemical properties and shelf life of toffee-like South Asian product (Dodol). The results showed broad range antifungal activity of fermented date fruit towards Aspergillus niger (90.85%), Aspergillus flavus (92.86%) Escherichia coli (13 mm) and Staphylococcus aureus (15 mm). The identified bioactive metabolites included propylene glycol (0.028 mmol mL−1), lactic acid (0.763 mmol mL−1), acetic acid (0.292 mmol mL−1), acetoin (0.046 mmol mL−1) and gamma-Aminobutyric acid (0.041 mmol mL−1). Fermented date fruit (125 g/kg) significantly (p < 0.05) extended the shelf life of Dodol for 19 days at 25 ± 2 °C in comparison to the control that showed mould growth after 12 days. The microbial growth was significantly reduced in the modified Dodol. A significant influence was observed in the physiochemical properties for modified Dodol such as increasing moisture and water activity and reducing the product firmness. No significant differences (p ≥ 0.05) were observed for the consumer acceptability between traditional and modified Dodol. The results indicated that the high antifungal activity is due to the presence of several bioactive metabolites. Moreover, the findings indicated the promising applications of fermented date fruit as functional ingredient to improve quality and the shelf life stability for confectionaries.